Tahlīl Masha'ib al Lughah al 'Araiyah fi thalabah Ta'lim al Riyādiyat - Ja’far Nasution; Rahma Hayati Siregar (IAIN Padangsidimpuan, 2022)
Analysis of Arabic learning difficulties in mathematics education students Arabic is one of the subjects studied in semesters one to two for all majors on the IAIN Padangsidimpuan campus, not only as a subject but as a daily language of instruction that must be applied by all students, as well as Tadris Mathematic students also use arabic. Most of the second semester students of Tadris Mathematic come from public schools who have never studied Arabic at all. Therefore they find it difficult to learn and understand Arabic. This research is a qualitative research with the method of analyzing the difficulties faced by the second semester students. The results of this research are that everything related to the difficulties faced by students when studying Arabic has internal and external factors. The conclusion of this research is that it is still possible for second semester students of Tadris Mathematics to study Arabic seriously in order to improve their Arabic and reduce the difficulties they face either internal or external factors